2016
DOI: 10.1080/10428194.2016.1190972
|View full text |Cite
|
Sign up to set email alerts
|

Association of DDX58 177 C > T polymorphism with decreased risk of Epstein–Barr virus-related nodular sclerosis classical Hodgkin lymphoma

Abstract: Classical Hodgkin lymphoma (cHL) is frequently related to Epstein-Barr virus (EBV) infection. Its malignant capacity is attributed to disruption of an EBV-host balance influenced by environmental and genetic drivers. EBV structures activate Type I interferon (IFN) pathway of the innate immunity, therefore, genetic polymorphisms could influence this response. We explored the impact of four single nucleotide polymorphisms (SNPs) on EBV-associated cHL susceptibility. Toll-like receptors 9 (TLR9_rs5743836), and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…RIG-I may have a protective role in classical Hodgkin lymphoma (cHL) in young patients yet support an immunosuppressive environment in older patients [ 60 , 61 ]. RIG-I single nucleotide polymorphism (SNP) have been associated with nodular sclerosis in EBV-positive younger age cHL patients [ 61 ].…”
Section: Rig-i In Ebv Associated Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…RIG-I may have a protective role in classical Hodgkin lymphoma (cHL) in young patients yet support an immunosuppressive environment in older patients [ 60 , 61 ]. RIG-I single nucleotide polymorphism (SNP) have been associated with nodular sclerosis in EBV-positive younger age cHL patients [ 61 ].…”
Section: Rig-i In Ebv Associated Malignanciesmentioning
confidence: 99%
“…RIG-I may have a protective role in classical Hodgkin lymphoma (cHL) in young patients yet support an immunosuppressive environment in older patients [ 60 , 61 ]. RIG-I single nucleotide polymorphism (SNP) have been associated with nodular sclerosis in EBV-positive younger age cHL patients [ 61 ]. While Satoh et al investigated RIG-I signaling in EBV-positive and EBV-negative cHL elderly patients found although RIG-I expression increased, no increase in IRF3 activation or IFN-β expression was reported in EBV-positive elderly cHL patients [ 60 ].…”
Section: Rig-i In Ebv Associated Malignanciesmentioning
confidence: 99%
“…A particular single nucleotide polymorphism (SNP) on Toll-Like Receptor 9 (TLR9) has been the center of multiple studies that analyzed its relation to lymphoma formation; this SNP is rs5743836 (TLR9-1237T>C). In the aforementioned studies, results have demonstrated that this SNP either shows no association with the risk of HL development or significantly increased the risk of developing HL and NHL [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HL shows variable trends that are significantly influenced by geographic, socioeconomic, racial, gender, and age differences [4]. Incidence is higher in more developed countries and among males, characteristically displaying a bimodal curve of incidence that is most significant for young adults (of age [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and those above 50 years of age [5,6]. Epidemiologic studies indicate that genetic and environmental factors both play essential roles in the pathogenesis of HL [7].…”
Section: Introductionmentioning
confidence: 99%